Carcinoma of the gall bladder: 8 year experience from a tertiary care centre, Punjab, India - Sharma, Mohit; Singh, Rachhpal (International Surgery Journal, 2019)
Background: Gall bladder carcinoma is the most common malignancy of biliary tract and one of the most aggressive gastrointestinal malignancies. The present study was conducted to know the clinical aspects, results and survival patterns after therapeutic interventions in patients of gall bladder cancer. Methods: The study is retrospective analysis of prospectively collected data of gall bladder cancer patients. Results: In 288 gall bladder cancer patient’s median age was 60 yrs. There were 219 females, 69 males (F:M=3.2:1). Median number of days from the onset of symptoms to presentation was 24.5 days. Majority of patients were stage IVB 162 (56.3%), least were stage I 3(1%). 192 (66.7%) patients received palliative treatment because of unresectable malignancy. 39 (13.5%) patients underwent noncurative surgical intervention. 57 (19.8%) patients underwent extended cholecystectomy. The median number of lymph nodes detected on histopathological examination was 4.5 (range 3-12). 21 patients (36.8%) had positive lymph nodes. Median follow up of all patients was 6 months (1-66 months). 27 (9.4%) patients survived till last date of follow up. Median survival time in groups undergoing extended cholecystectomy, noncurative surgery, chemotherapy alone was 12, 8 and 4 months respectively. The difference in median survival time between the groups was statistically significant, Log rank (Mantel-Cox) χ2=109.78, p=0.00. Conclusions: Carcinoma of the gall bladder predominately affects females. Majority of patients had delayed presentation, stage IVB. Extended cholecystectomy is the only effective treatment to achieve long term survival.